Genetic analysis of the 2019 coronavirus pandemic with from Real-time reverse transcriptase polymerase chain reaction (2020)
Corona viruses (CoV) are known to cause extreme pandemics in the globe. The year 2020 will be a pandemic with the spread of the novel coronavirus (SARS-CoV-2) across the globe. Coronavirus 2019 (COVID-19) has been a part of our scary life for more than a quarter of a year in 2020. The Wuhan market and China have been the most commonly used terms in the world for at least a quarter of 2020. A zoonotic coronavirus has entered organisms to affect organisms for the third season in several centuries. CoV is a global pandemic prompted a drastic and rapid reconfiguration of society. CoV have extraordinary broad genomes of about 30 kilobases of RNA. There is no genetic relationship between the SARS-CoV, MERS and SARS-CoV-2. For health care strategies and for anticipating and preventing potential outbreaks, adequate description of the international spread of COVID-19 virus is imperative. The WHO has declared COVID-19 as endemic to pandemic in the first trimester of 2020. The biggest issues for diagnosis COVID-19 is not established apart from Real-time reverse transcriptase polymerase chain reaction (RT-PCR). In order to monitor the COVID-19 pandemic, testing of active SARSCoV-2 infections is a fundamental public health method. The vast use of SARS-CoV-2 RT-PCR tests around the world has led to increased availability of test kits, which is also a major bottleneck. The technique RT-PCR was generally agreed in the present scenario to detect SARSCoV-2 in the human body. This review discusses about the importance of molecular technique for diagnosing the pandemic disease of 2019. In conclusion, RT-PCR was found to be an apt technique for identification of SARS-CoV-2.